BIOM-36. SERIAL ASSESSMENT OF MEASURABLE RESIDUAL DISEASE IN MEDULLOBLASTOMA LIQUID BIOPSIES. (12th November 2021) - Liu, Anthony Pak-Yin; Smith, Kyle; Kumar, Rahul; Paul, Leena; Lin, Tong; Maass, Kendra; Pajtler, Kristian; Bihannic, Laure; Orr, Brent; Ellison, David; Gilbertson, Richard; Onar-Thomas, Arzu; et al.
Abstract: Medulloblastoma is the most common malignant brain tumor in children. Despite the use of contemporary multi-modal therapy, up to one-third of patients will succumb to disease progression. Conventional response monitoring is based on magnetic resonance imaging and cerebrospinal fluid (CSF) cytology and a marker for measurable residual disease (MRD) is lacking. In this study, we show the clinical utility of profiling CSF-derived cell-free DNA (cfDNA) as a biomarker of MRD based on a sizable cohort of children with medulloblastoma enrolled on a prospective, multi-center, risk-adapted trial (SJMB03; NCT00085202). A total of 476 CSF samples were serially collected from 123 patients by lumbar puncture at post-operative baseline, during therapy, and at regular surveillance after completion of therapy. Using low-coverage whole-genome sequencing (lcWGS), tumor-associated copy-number alterations in CSF-derived cfDNA were investigated as an MRD surrogate for correlation with clinical features and outcomes. MRD was detected in post-operative baseline CSF samples for 85% and 54% of patients with metastatic and localized disease, respectively. The number of MRD-positive patients declined with therapy, yet those with persistent MRD detected at the end of therapy (20 of 68 CSFs at this timepoint) had significantly higher risk of disease progression (hazard ratio 8.94, 95%CI 4.10-19.49; log-rank p< 0.0001). Importantly, MRD-positivity from routine surveillance samples often preceded radiographic progression by more than 3 months. Comparative analyses of copy-number variations obtained from serial CSF samples enabled identification of relapse-specific alterations and early detection of relapse-dominant clones. Overall, our findings advocate for the routine incorporation of CSF-derived liquid biopsies in future medulloblastoma trials.